Yard crane scheduling problem in a container terminal considering risk caused by uncertainty. (January 2019) - He, Junliang; Tan, Caimao; Zhang, Yuting
Highlights: The extra loss caused by uncertainty is measured. A MIP model under uncertainty is formulated considering a lot of uncertain scenarios. A GA-based framework combined with three-stage algorithm is proposed. Abstract: In a container terminal, the arriving times and handling volumes of the vessels are uncertain. The arriving times of the external trucks and the number of containers which are needed to be brought into or retrieved from a container terminal by external trucks within a period are also uncertain. Yard crane (YC) scheduling is under uncertainty. This paper addresses a YC scheduling problem with uncertainty of the task groups' arriving times and handling volumes. We do not only optimize the efficiency of YC operations, but also optimize the extra loss caused by uncertainty for reducing risk of adjusting schedule as the result of the task groups' arriving times and handling volumes deviating from their plan. A mathematical model is proposed for optimizing the total delay to the estimated ending time of all task groups without uncertainty and the extra loss under all uncertain scenarios. Furthermore, a GA-based framework combined with three-stage algorithm is proposed to solve the problem. Finally, the proposed mathematical model and approach are validated by numerical experiments.